The Teacher is Not Enough: Why Achievement Motivation Trumps Teaching Styles in Islamic History Classrooms - Nurhamzah Nurhamzah; Yuni Purnama Sari; Hariman Surya Siregar; Irfan Ahmad Zain (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2026)
The main focus of modern education is to enable students to learn independently, yet many students remain heavily dependent on teachers, including in the specific context of Islamic Cultural History learning. This study aims to empirically test and compare whether the teacher's teaching style or the student's achievement motivation has a stronger influence on learning independence when tested simultaneously. Using a quantitative approach with an explanatory associative design, the researchers distributed questionnaires to 104 students at Islamic Senior High School I'anatut Tholibin Margahayu-Bandung-Indonesia and analyzed the data using multiple regression via SPSS 26. The results demonstrate that while both factors have a significant positive impact, achievement motivation is the most dominant predictor of independence in studying Islamic historical narratives, as shown by its higher standardized beta coefficient. This suggests that the narrative and value-heavy nature of Islamic Cultural History (SKI) requires students to have strong internal drive to internalize historical meanings, making their own ambition to achieve more decisive for autonomy than the teacher's external delivery. In conclusion, internal psychological drive is more critical than external pedagogical methods for mastering Islamic Cultural History. Therefore, to foster autonomous learners in Islamic Cultural History, schools should integrate technical programs like 'Historical Role-Play Reflection' and 'Progressive Narrative Mapping' into their curriculum. These initiatives shift the focus from rote memorization to student-led goal-setting, allowing learners to independently analyze historical decision-making and build the self-efficacy needed to interpret historical values.